A review of several myopathy related to mitochondrial dysfunction - Wang Nan; Oleksandr Motuziuk; Dmytro Davydenko (Нотатки сучасної біології, 2022)
The balance of protein production and consumption in muscles depends to a large extent on normal mitochondrial function. Mitochondrial dysfunction is inseparable from the occurrence of myopathy. This study explores the relationships between statin-induced myopathy, steroid myopathy, and skeletal muscle illness caused by alcohol addiction, as well as the relationship between these conditions and mitochondrial abnormalities. Web of Science (WOS) central archive was analyzed for alcoholic myopathy research papers from 1999 to 2021, CiteSpace and WOS databases were used for evaluation the number of written articles, distribution of publications by region, research organizations, co-cited lit-erature analysis, and keyword identification. A total of 1,255 publications were collected after screening, with the number of published articles continually increasing. The annual average number of publications is 54.56. Six countries publish the majority of the literature. The United States has published 383 papers in total, which places it first among all countries. It also has the most centrality, meaning that other countries value its scientific achievements more. There are 34 core authors and 238 papers published. Through cluster analysis, there are 9 categories that are significant clusters. Key words of co-occurrence research show that keywords such as nanoparticles, apoptosis, mitochondrial disorders, and inflammation are very common.